Serum Hs-Crp And Uric Acid As Indicator Of Severity In Preeclampsia - ANIL BARGALE; JAYASHREE V. GANU; DHIRAJ J. TRIVEDI; NITIN NAGANE; RAKESH MUDARADDI; APARNA SAGARE (International Journal of Pharma and Bio Sciences, 2011)
The aim of the present study is to correlate hs-CRP and uric acid levels in preeclamptic women. This study was performed on three groups; mild preeclampsia (n=17), severe preeclampsia (n=13) and healthy pregnant women as controls (n=30). Hs-CRP and uric acid levels were measured in maternal serum by latex turbidimetric method and Uricase-PAP method respectively. In this study we found serum hs-CRP and Uric acid levels were higher in preeclamptic women (3.733±1.096, 8.007±1.077) as compared to normotensive pregnant women (1.216±0.552, 5.50±1.103). Similarly, serum hs-CRP and uric acid levels were significantly elevated in women with severe preeclampsia (4.769±0.807, 9.042±0.650) than mild preeclampsia cases. The positive and significant correlations were found in hs-CRP/Blood Pressure, Uric Acid /Blood Pressure and hs-CRP/Uric Acid. Our results shows that serum hs-CRP and Uric Acid levels have increased as disease progressed from mild to severe condition. Therefore, hs-CRP can be an additional marker to predict severity of disease.